Crystal and molecular structure determination, TGA, DTA, and infrared and Raman spectra of rubidium nitroprusside monohydrate, Rb₂[Fe(CN)₅NO] . H₂O - Soria, Delia Beatriz (1999)
The crystal structure of rubidium nitroprusside monohydrate, Rb₂[Fe(CN)₅NO] . H₂O, has been determined from X-ray diffraction data and refined using direct and Fourier methods to R = 0.066 and Rw = 0.075, employing 1894 independent reflections with I > 3 (I). The substance crystallizes in the monoclinic space group C2/c (C62h), with a = 13.987(2), b = 10.241(1), c = 18.151(1) Å, β = 110.94°, and Z = 8. Anions are located at C1 sites, one per asymmetric unit, and are slightly distorted octahedra. TGA, DTA, FTIR, and FTIR Raman results were interpreted on the basis of the formula of the compound, its crystal structure, and the behavior of other nitroprussides.